Influence of cigarette smoking on bone mineral density in postmenopausal women with estrogen deficiency in menstrual history (Journal of Health Sciences, 2014)
Introduction: Estrogen deficiency leads to bone mass loss and increased risk for osteoporosis. The aim of this study was to examine influence of cigarette smoking on bone mineral density in postmenopausal women with estrogen deficiency in menstrual history.Methods: The total of 100 postmenopausal women living in Sarajevo area, aged 50-65 years, with estrogen deficiency in menstrual history participated in this prospective study. The subjects were divided in two groups, examination and control group, based on bone mineral density values. The women in the examination group had osteoporosis while in the control group were women with osteopenia or normal bone mineral density. Bone mineral density was measured at the lumbar spine and proximal femur by Dual–Energy X–ray Absorptiometry using Hologic QDR-4000 scanner. Smoking habits were assessed for each subject.Results: The average number of cigarettes smoked per day in women with estrogen deficiency in menstrual history was 14.86 in the examination group and 4.67 in the control group. The difference in the average number of cigarettes smoked per day between the two groups was statistically significant (p <0.01). The coefficient of linear correlation between T score and the number of cigarettes smoked per day among women with estrogen deficiency in menstrual history in the examination group was statistically significant (p<0.01). The coefficient of linear correlation between T score and the number of cigarettes smoked per day among women with estrogen deficiency in menstrual history in the control group was statistically significant ( p<0.05).Conclusion: Results of this study suggest that cigarette smoking has negative impact on bone mineral density and that healthy lifestyle (no smoking) has the potential to reduce bone loss in postmenopausal women with estrogen deficiency in menstrual history.